Konstitusionalitas Dewan Pers Pasca Putusan Mahkamah Konstitusi terhadap Judicial Review UU Pers - Zacky Antony (UNIB Press, 2022)
The issue of the constitutionality of the Press Council has received a lot of attention in recent years. Especially since the Press Council issued regulations in the press sector. Among other things, the Press Council's regulations governing the competency standards of journalists and the Press Council's regulations governing the verification of media companies include administrative verification and factual verification. Many parties consider that the issuance of regulations in the press sector has exceeded the authority of the Press Council as regulated in Law Number 40 of 1999 concerning the Press which became the basis for the formation of the Press Council. The decision of the Constitutional Court (MK) on the petition for judicial review of Law Number 40 of 1999 concerning the Press has had an impact on the life of the national press. The Constitutional Court's decision to reject the judicial review of the Press Law as a whole has confirmed the constitutionality of the Press Council in issuing regulations in the press sector as a reference in the operational level of journalistic work for journalists. This is important so that there is no doubt and confusion in the life of the national press.